2014
DOI: 10.1007/s00158-014-1118-7
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of exact multi-load topology optimization – stress-based least-volume trusses (generalized Michell structures) – Part I: Plastic design

Abstract: In this two-part paper, Michell's century-old stress-based single-load truss topology optimization paper is extended to multiple load conditions. In Part I, so-called 'optimal plastic design' of multi-load trusses is reviewed, which is based on ultimate (limit or collapse) load principles and requires only statical admissibility of the solution. However, its connections to 'optimal elastic design' will be explained, and these will be used in Part II for the full extension of Michell's theory to elastic multi-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…17a, b), cases where 0 ≤ θ ≤ π 2 will be considered. Two special cases of this, with θ = 0 and θ = π 4 , were studied by Rozvany et al (2014). First the component load-cases are calculated; the sum component load-case 2 P * 1 = (P 2 + P 1 )/ √ 2 contains a point load of magnitude Q and inclined at an angle of θ − π 4 (Fig.…”
Section: Funding Informationmentioning
confidence: 99%
“…17a, b), cases where 0 ≤ θ ≤ π 2 will be considered. Two special cases of this, with θ = 0 and θ = π 4 , were studied by Rozvany et al (2014). First the component load-cases are calculated; the sum component load-case 2 P * 1 = (P 2 + P 1 )/ √ 2 contains a point load of magnitude Q and inclined at an angle of θ − π 4 (Fig.…”
Section: Funding Informationmentioning
confidence: 99%
“…Using the British Standard load cases (2a-2c), and with Assumptions 1, 2 and 3 removed, a parameter governing the optimal layout can be identified. To establish this, Rozvany's work on optimization with multiple load cases (Rozvany et al 2014) and the superposition method of Rozvany and Hill (1978) will be used. Figure 1a shows a graphical depiction of the load cases in (2a-2c).…”
Section: Parameter Governing the Optimal Layout R Vhmentioning
confidence: 99%
“…However, this approach requires there to be 2 n load cases, with n being a positive integer. Following Rozvany et al (2014), a fourth, dummy load case p 4 can be introduced, comprising vertical loads V − V . According to Property 3 in Rozvany et al (2014), since V > 0, the optimized result for the problems shown in Fig.…”
Section: Parameter Governing the Optimal Layout R Vhmentioning
confidence: 99%
“…This is because plastic yielding of members can occur, allowing forces within the structure to redistribute as necessary. Theoretical issues associated with the plastic multiple load case formulation are considered in more depth by Rozvany et al (2014).…”
Section: Basic Formulationmentioning
confidence: 99%